Peripheral CCL2 induces inflammatory pain via regulation of Ih currents in small diameter DRG neurons - Li, Lamei; Liu, Yuanying; Hu, Wenchao; Yang, Jing; Ma, Suibin; Tian, Zhicheng; Cao, Zixuan; Pan, Kunqing; Jiang, Ming; Liu, Xia; Wu, Shengxi; Luo, Ceng; et al. (Frontiers in Molecular Neuroscience, 2023)
The C-C motif chemokine ligand 2 (CCL2) has been implicated in chronic pain, but its exact mechanism of peripheral sensitization is unknown. In this study, we aimed to clarify the mechanism of CCL2 regulation of ion channels. Our behavioral experiments revealed that ZD7288, a blocker of Ih current, can inhibit CFA and CCL2-mediated mechanical and thermal nociceptive sensitization. Furthermore, patch clamp studies demonstrated that CFA-induced peripheral sensitization primarily affects the excitability of small-diameter DRG neurons. Further studies revealed that inflammatory pain caused by CFA or incubation of DRG with CCL2 mainly affected Ih currents in small-diameter DRG neurons, which were blocked by co-incubation CCR2 antagonist INCB3344 or adenylate cyclase inhibitor SQ22536. Immunohistochemical staining showed that both intraplantar injection of CFA as well as DRG injection of CCL2 resulted in significant upregulation of CCR2+/HCN2+ expression. In conclusion, we suggest in the inflammatory pain state, CCL2 can act on small-diameter DRG neurons, leading to upregulation of HCN2 expression and consequently Ih, which in turn leads to neuronal hyperexcitability.